Factors Related to Family Attitudes in Helping Patients Adapt to Meet Basic Needs and Prevention of Post-Stroke Depression - Elmukhsinur, Elmukhsinur; Rosy, Alice; Kurniadi, Rizki (Adi Husada Nursing Journal, 2024)
Stroke is the leading cause of disability and death. One of the major problems faced by individuals who have a stroke is physical disability and depression. Strokes often interfere with the ability to move, speak, and perform daily activities. It can lead to dependence on others for self-care. The study aimed to find out the relationship between gender, education, experience, knowledge, and family attitudes in helping patients adapt to meet basic needs and prevent post-stroke depression at the Indrasari Rengat Hospital. The design of the research was a cross-sectional survey with a sample of 54 respondents in the nerve center and intensive care room of the Indrasari Rengat hospital unit from May 4 to August 9, 2023.A data collection tool using a questionnaire that contains questions about adaptation in the fulfillment of basic needs and prevention of post-stroke depression, as well as statements of family attitudes toward meeting basic needs and post-stroke prevention. The data analysis in this study is descriptive analysis and bivariate analysis with a chi-square test. The results show that there is a meaningful relationship between gender, experience, knowledge, and family attitudes in helping patients adapt to meet basic needs and prevent post-stroke depression. Family attitudes toward helping stroke patients adapt and prevent post-stroke depression are generally positive.